YIA 1 Toll-like receptor 3 expression is increased in atherosclerosis and confers protection against early atherosclerotic lesion development and weight gain in apolipoprotein E deficient mice. Issue 20 (23rd September 2011) - Cole, J E; Navin, T J; Cross, A J; Goddard, M E; Alexopoulou, L; Mitra, A J; Davies, A H; Flavell, R A; Feldmann, M; Monaco, C
Abstract : Introduction: Previous studies have assigned detrimental roles to toll-like receptors (TLR) in cardiovascular disease. Recently we described a novel protective role for TLR3 in vivo in intimal hyperplasia. Aim: Using human and murine systems we investigated the consequence of TLR3 signalling in atherosclerosis. Methods and Results: We compared the responses of human atheroma-derived smooth muscle cells (AthSMC) and control aortic smooth muscle cells (AoSMC) to various TLR ligands. AthSMC exhibited a specific increase in TLR3 expression and TLR3-dependent functional responses. Interestingly, exposure to the TLR3 ligand poly (I:C) induced both pro- and anti-inflammatory gene expression in vitro in AthSMC and in vivo in vascular tissues. We examined the role of TLR3 signalling in atherosclerosis in vivo using 15- and 30-week ApoE−/− and ApoE−/−TLR3−/− mice fed a chow diet. Aortic root lesion area was significantly increased in ApoE−/−TLR3−/− mice compared to ApoE−/− mice at 15- (p=0.035) but not 30-weeks of age (p>0.05) suggesting that TLR3 is protective in early but not more advanced stages of lesion development. The absence of an exogenous viral stimulus implicates an endogenous vasculoprotective TLR3 ligand. TLR3 deficiency did not affect lesional macrophage or collagen content nor cholesterol levels. Intriguingly, high-fat feeding for 15-weeks induced increased weight gain in ApoE−/−TLR3−/− mice compared to ApoE−/− mice (p=0.047). Conclusions: Collectively, our data describe for the first time a protective role for TLR signalling in atherosclerosis and suggest that an endogenous TLR3 ligand may mediate the observed protection. Moreover, genetic deletion of TLR3 leads to susceptibility to high-fat diet induced obesity.